1999
DOI: 10.1159/000052868
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Environmental Toxins in the Pathophysiology of Endometriosis

Abstract: Environmental contaminants that are known to disrupt steroid action can influence the development of reproductive diseases. Our group has focused on whether 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD or dioxin) can disrupt steroid regulation of endometrial matrix metalloproteinase (MMP) expression. The MMPs regulate extracellular matrix turnover in normal tissues, but the inappropriate expression of these enzymes is associated with numerous disease states that involve invasive processes. We have previously show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 16 publications
2
60
0
1
Order By: Relevance
“…Although endometriosis is not normally a life-threatening condition, the severity of disease, including multiple organ invasion, noted in the TCDD-exposed primate colony described by Rier et al [30] suggested to us that TCDD may disrupt the regulation of the endometrial MMP system. Indeed, we found that following short-term exposure of control human endometrium to TCDD, the capacity of endometrial fragments to invade the peritoneal wall of nude mice in our experimental endometriosis model was greatly enhanced [28]. Since a woman's exposure to progesterone is recognized as a negative risk factor for the development of endometriosis, it is important to determine whether TCDD may act to disrupt key elements of progesterone action in the reproductive tract.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although endometriosis is not normally a life-threatening condition, the severity of disease, including multiple organ invasion, noted in the TCDD-exposed primate colony described by Rier et al [30] suggested to us that TCDD may disrupt the regulation of the endometrial MMP system. Indeed, we found that following short-term exposure of control human endometrium to TCDD, the capacity of endometrial fragments to invade the peritoneal wall of nude mice in our experimental endometriosis model was greatly enhanced [28]. Since a woman's exposure to progesterone is recognized as a negative risk factor for the development of endometriosis, it is important to determine whether TCDD may act to disrupt key elements of progesterone action in the reproductive tract.…”
Section: Discussionmentioning
confidence: 87%
“…These results strongly suggest that reduced endometrial expression of progesteroneresponsive genes and proteins, due to decreased expression of PR-B, may be an important contributing factor to an individual's overall risk for developing endometriosis. Although the cellular mechanism(s) associated with the development of reduced endometrial responsiveness to progesterone among endometriosis patients is not completely understood, our experimental data suggests that acute exposure of human tissue or cells to TCDD can dramatically reduce both PR-B expression and progesterone-mediated TGF-β2 expression, contributing to a more invasive endometrial phenotype in our experimental endometriosis model [20,[27][28][29].A possible role of environmental contaminants with dioxinlike activity in the development of endometriosis emerged with the demonstration that the incidence and severity of spontaneous endometriosis in rhesus monkeys was increased following dietary exposure to TCDD [30].Although two recent epidemiologic studies demonstrated an increased level of dioxin-like compounds in the serum of women with endometriosis compared to disease-free women [31,32], other epidemiologic examinations have been less definitive [33,34]. Since human and animal exposures actually begin in utero, when toxicant sensitivity is greatest, developing a clearer understanding of the potential effects of TCDD and other environmental contaminants will likely require examining the impact of early, developmental exposure.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…A perda da sensibilidade endometrial à progesterona é reconhecidamente um potencial fator causal da endometriose. Durante o ciclo menstrual, conforme os níveis de progesterona diminuem na fase secretória, percebemos um aumento de citocinas e quimiocinas proinflamatórias e de MMPs, preparando o endométrio para o intenso processo inflamatório da menstruação 13,14 . Além disso, complexos PCBs/TCDD + receptores AhR podem ativar genes proinflamatórios de citocinas e quimiocinas, podendo propiciar um padrão crônico de sinalização pro-inflamatória que ocasionaria em uma interrupção da função endometrial normal.…”
unclassified
“…Because of the potent anti-inflammatory action of progesterone, reduced sensitivity to this steroid could contribute to the autoimmune nature of endometriosis, as well as to more specific local and systemic changes i.e., during the menstrual cycle, as progesterone levels fall into the secretory phase, increased proinflammatory cytokines and chemokines and matrix metalloproteinase are seen, in preparation for the high inflammatory process of menstruation [88,89] Furthermore, TCDD together with estradiol is known to further potentiate the proinflammatory effect, raising the presence of RANTES (Regulated on Activation, Normal T Cell Expressed and Secreted) and MIP-1a (macrophage protein 1-alpha), entailing the ability to invade stromal endometrial cells and on the spot express matrix metaloproteinases-2 and -9 [90]. Developmental exposure of mice to TCDD elicits a similar uterine phenotype in adult animals as observed in women with endometriosis, since female mice which have been in utero exposed to TCDD, and again during the development of reproductive potential demonstrated a progressive loss of both progesterone receptors expression [91].…”
mentioning
confidence: 99%